2016
DOI: 10.1590/1806-9282.62.05.421
|View full text |Cite
|
Sign up to set email alerts
|

Ductal carcinoma in situ of the breast: Evaluation of main presentations on magnetic resonance imaging compared with findings on mammogram and histology

Abstract: Ductal carcinoma in situ of the breast: evaluation of main presentations on magnetic resonance imaging compareD with finDings on mammogram anD histology rev Assoc MeD brAs 2016; 62 (5) Objective: The purpose of this study was to evaluate the various morphologies and kinetic characteristics of the ductal carcinoma in situ (DCIS) on breast magnetic resonance imaging (MRI) exam, to establish which are the most prevalent and to determine the effectiveness of the method in the detection of DCIS.Method: A prospectiv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 33 publications
0
1
0
Order By: Relevance
“…Regarding the imaging feature, previous studies have suggested that breast MRI was highly sensitive for detecting and evaluating breast cancer of various types. DCIS often manifests as non-mass-like enhancements with segmental or ductal distribution, and presents clumped internal architecture in the MRI imaging 14 , 18 21 . The common manifestation of DCIS included lump as well as segmental distribution in the current study.…”
Section: Discussionmentioning
confidence: 99%
“…Regarding the imaging feature, previous studies have suggested that breast MRI was highly sensitive for detecting and evaluating breast cancer of various types. DCIS often manifests as non-mass-like enhancements with segmental or ductal distribution, and presents clumped internal architecture in the MRI imaging 14 , 18 21 . The common manifestation of DCIS included lump as well as segmental distribution in the current study.…”
Section: Discussionmentioning
confidence: 99%